PENGARUH TERAPI MUROTTAL AL-QUR'AN TERHADAP TINGKAT KECEMASAN PASIEN PRE ANGIOGRAFI KORONER - Wati, Linda; Nurhusna, Nurhusna; Mawarti, Indah (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2020)
Coronary angiography measures affect patients. Murottal al-quran therapy can be used to reduce anxiety levels. Murottal works on the brain where when stimulated by stimulation of murottal therapy the brain will produce neuropeoptide substances that can pleasure and comfort to reduce the anxiety felt by patients. The aim of this study was to determine the influence of of murottal al-qur'an therapy with anxiety level of coronary before angiography patients in the Cath Lab room of Raden Mattaher Hospital Jambi. The research design used quantitative with design of pre test post test with control group design. The sampling technique used purposive sampling with sample of 20 people located in the Cath Lab Room of Raden Mattaher Jambi and data collection using ZSAS questionnaire processing data using paired T-test and Independent T-test. The mean value of anxiety intervention group before murottal therapy is 62.80 (moderate anxiety) and after murottal therapy was reduced to 49.20 (mild anxiety). Whereas the control group before murottal therapy was given average value of 58.30 (mild anxiety) and after being given murottal therapy there was an increase to 62.80 (moderate anxiety). There was influence of murottal al-qur'an therapy with anxiety level of coronary before angiography patients in the Cath Lab room of Raden Mattaher Hospital Jambi in 2019. So this murottal al-qur'an therapy can be used as intervention to overcome anxiety before patients coronary angiography.